Studies on breath methane: the effect of ethnic origins and lactulose. Issue 11 (November 1980) - Pitt, P; de Bruijn, K M; Beeching, M F; Goldberg, E; Blendis, L M
Abstract : The prevalence of methane production in an adult population of 256 subjects was 41%, but it was significantly higher in females (49%), than males (33%). When the population was subdivided into ethnic groups. Caucasians (48%) and Black (45%) had significantly more methane producers than Orientals (24%) and Indians (32%). when the ethnic groups were analysed by sex, female Caucasians had the highers prevalence (58%), significantly more than Caucasian males, Oriental males, and females and Indian males. In contrast with previous studies, a single dose of lactulose was found to significantly increase breath methane concentrations in six out of 12 methane producers, but not in 25 non-methane producers from the population study. In conclusion, any studies on breath methane must take into consideration the ethnic origin of the subjects and, contrary to previous advice, substrate intake, especially undigestible carbohydrates. Furthermore, a single breath sample may miss up to one-fifth of methane producers.